Financial Literacy and the Use of Financial Ratios in Improving MSME Performance in Indonesia: JEL Classification: G53, G32, M41, L26, O16 - Tanto Tanto (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth and employment in Indonesia, yet their performance is often constrained by limited financial management capabilities. This study aims to synthesize existing literature on the role of financial literacy and the use of financial ratios in improving MSME performance. Using a structured literature review approach, this study analyzes peer-reviewed articles, academic publications, and institutional reports to identify key patterns and relationships among the variables. The findings indicate that financial literacy serves as a foundational capability that enables MSME actors to understand financial concepts, manage resources efficiently, and make informed decisions. Meanwhile, financial ratios function as practical analytical tools that provide measurable insights into business performance, including liquidity, profitability, solvency, and operational efficiency. The study further reveals a strong synergistic relationship between financial literacy and the use of financial ratios, where financial knowledge enhances the ability to apply ratio analysis effectively, and the use of ratios reinforces financial understanding through practice. This integration contributes to improved financial discipline, better strategic planning, and increased access to external financing. Additionally, the combined application of these factors strengthens MSME resilience and adaptability in a dynamic and competitive business environment. The study highlights the importance of promoting both financial literacy and financial analysis skills as part of MSME development strategies. These findings provide valuable implications for policymakers, educators, and practitioners in designing targeted interventions to enhance MSME sustainability and economic contribution.